Correction: In vitro analysis of partially hydrolyzed guar gum fermentation differences between six individuals. Issue 3 (1st March 2016) - Carlson, Justin; Esparza, Julian; Swan, Jonathon; Taussig, David; Combs, Jerry; Slavin, Joanne
Abstract : Correction for ' In vitro analysis of partially hydrolyzed guar gum fermentation differences between six individuals' by Justin Carlson, et al., Food Funct., 2016, DOI: 10.1039/c5fo01232e.